Synthesis of furano[2,3-c] /pyrrolo[2,3-c]coumarins and synthesis of 1(H)-[1]benzopyrano[3,4-b][1]benzopyrano[3’,4’-d] furan-7(H)-ones /1(H)-[1]benzopyrano[3,4-b][1]benzopyrano [3’,4’-d]pyrrole-7(H)-ones - Pandya, Mahesh K.; Chhasatia, Mehulsinh R.; Vala, Nileshkumar D.; Parekh, Tapan H. (Journal of Drug Delivery and Therapeutics, 2019)
A series of synthesis of various 1-aryl-furano[2,3-c] and 1-phenyl-2-methyl-furano [2,3-c]coumarins;1-aryl-pyrrolo[2,3-c]and1-phenyl-2methylpyrrolo[2,3c]coumarins; 1aryl1H1] benzopyrano[3,4,-b][1]benzpyrano [3’,4’-d]furan-7H-ones and 1-aryl-1(H)-[1]benzopyrano[3,4,-b][1]benzpyrano[3’,4’-d]pyrrole-7(H)-ones. 1-Aryl-furano [2,3-c]coumarins and 1-phenyl-2-methyl-furano[2,3-c]coumarin have been synthesized by reacting 3-hydroxy coumarin with various 2-aryl-1-nitro-ethenes and 1-phenyl-2-nitro-propene respectively in the presence of piperidine and methanol as solvent. 1-Aryl-pyrrolo [2,3-c]coumarins and 1-phenyl-2-methyl-pyrrolo[2,3-c] coumarin also have been synthesised by reacting 3-amino coumarin with  various 2-aryl-1-nitro-ethenes and 1-phenyl-2-nitro-propene respectively in the presence of piperidine and methanol. The formation of furan and pyrrole nucleus in all above compounds follows Nef reaction mechanism. Using the Nef reaction, synthesis of various 1-aryl-1(H)-[1]benzopyrano[3,4,-b][1]benzpyrano[3’,4’-d]furan-7(H)-ones have been carried out  by reacting various 4-hydroxy coumarins with various 3-nitro-2-aryl-2H-[1]benzopyrans in the presence of piperidine and methanol. Similarly synthesis of various 1-aryl-1(H)-[1]benzopyrano[3,4,-b][1]benzpyrano [3’,4’-d]pyrrole-7(H)-ones also have been carried out by reacting various 4-hydroxy coumarins with various 3-nitro-2-aryl-2H-[1]benzopyrans in the presence of ammoniun acetate  and acetic acid.Keywords: Furan, Pyrrolo,Coumarin, Benzopyrano.